CHARACTERISTICS OF COMORBIDITIES IN OVERWEIGHT AND OBESE CHILDREN AND ADOLESCENTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Childhood and adolescent obesity is a growing global health problem that significantly increases the risk of developing various comorbid conditions. These include metabolic, cardiovascular, endocrine, orthopedic, and psychological disorders. The presence of such comorbidities at a young age not only affects physical and emotional development but also increases the likelihood of chronic diseases in adulthood. This article reviews the key features of comorbid pathologies associated with excess body weight in children and adolescents and highlights the importance of early diagnosis and multidisciplinary intervention.